Research on historical deformation and rock layer water content variation in large open-pit mining areas based on SBAS and MatDEM - Geng, Jiabo; Liu, Cunyang; Lan, Xiang; Wang, Yunmin; Wang, Xing; Wang, Xiaobing (Frontiers in Earth Science, 2025)
In order to study the characteristics of settlement and deformation evolution of large open pit to underground mine quarries in China, and to analyse the changing law of volumetric water content of overburden rock layers at different mining stages. Based on 267 images from Sentinel-1A over a period of 10 years from 2015 to 2024, the SBAS-InSAR technology was used to analyze the subsidence situation of a mine in Jiangxi Province, and this was validated through discrete element numerical simulation. The results show that: (1) the deformation of the quarry is dominated by subsidence, and it is now in the stage of accelerated deformation, with the maximum subsidence reaching −168 mm, which is located at the eastern part of the quarry, in the area of high and steep slopes. (2) The settlement deformation of the mining field shows a clear positive correlation with underground mining. In 2015–2018, the settlement deformation is relatively slow, but in 2019–2024, as underground mining continues to advance, the surface settlement is obvious. From 2015 to 2024, more than 50% of the area in the mining zone experienced cumulative settlement deformation exceeding 75 mm. (3) Surface subsidence is the external result of the deformation of deep rock strata and sudden changes in water content. The mining of mineral chambers and pillars leads to the development of pores and fractures in the rock layers, further affecting changes in the volumetric water content. During the first rock layer collapse, the volumetric water content of the rock layers in the mining area is 40.3%, while during large-scale rock layer collapses, it is 44.8%. (4) The increase in volumetric water content of rock layers is one of the reasons for the instability of the rock layers. As the water content increases, the matrix suction gradually decreases to a limiting value of 1 kPa, while the permeability coefficient progressively increases to 3.71 × 10−6 m/s, resulting in the occurrence of rock layer collapse. This study indicates that the changes in the volumetric water content of rock layers during the transition from open-pit to underground mining are significantly associated with surface subsidence. The research findings can provide a theoretical basis for geological disaster warning and optimization of mining plans in similar mines.